2021
DOI: 10.1177/0969733020976185
|View full text |Cite
|
Sign up to set email alerts
|

Conscientious objection to medical assistance in dying in rural/remote nursing

Abstract: In 2016, the Supreme Court of Canada legalized medical assistance in dying in Canada. Similar to jurisdictions where this has been a more long-standing option for end-of-life care, the Supreme Court’s decision in Canada included a caveat that no healthcare provider could be compelled to participate in medical assistance in dying. The Canadian Nurses Association, in alignment with numerous ethical guidelines for healthcare providers around the globe, maintains that nurses may opt out of participation in medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
0
4
0
2
Order By: Relevance
“…Broadly speaking, reasons for when they choose to participate, limit the degree of their participation, or engage in nonparticipation in MAiD processes were rooted in conscience and non-conscience-based reasons. Personal values and ethics and the need for moral coherence created conscience-based reasons and, legal and professional risk, patient factors, personal competence, use of other end-of-life care options, and emotions created non-conscience-based reasons [ 43 ]. Moreover, as Brown et al suggest in their work [ 3 , 32 ], the participants in this study indicated that as they engaged in and integrated new personal and professional knowledge and were exposed to new experiences, their perspectives and actions changed.…”
Section: Discussionmentioning
confidence: 99%
“…Broadly speaking, reasons for when they choose to participate, limit the degree of their participation, or engage in nonparticipation in MAiD processes were rooted in conscience and non-conscience-based reasons. Personal values and ethics and the need for moral coherence created conscience-based reasons and, legal and professional risk, patient factors, personal competence, use of other end-of-life care options, and emotions created non-conscience-based reasons [ 43 ]. Moreover, as Brown et al suggest in their work [ 3 , 32 ], the participants in this study indicated that as they engaged in and integrated new personal and professional knowledge and were exposed to new experiences, their perspectives and actions changed.…”
Section: Discussionmentioning
confidence: 99%
“…Por eso, es necesario revisar hasta qué punto cuando un profesional hace objeción de conciencia, su negativa condiciona la actividad asistencial de otros trabajadores (Bouthillier & Opatrny, 2019;Wicclair, 2019;McDougall et al, 2022;Myskja, & Magelssen, 2018;Shanawan, 2016). Además, pueden producirse conflictos éticos respecto a la justicia distributiva (Panchuk & Thirsk, 2021;Schiller, 2017;Dobrowolska et al, 2020;Wester, 2015;Eberl, 2019). Si estas problemáticas se producen en un contexto de objeción institucional (Shadd & Shadd 2019;Hempton, 2021), las probabilidades de que se produzcan estos conflictos aumentan.…”
Section: Introduccio Nunclassified
“…For this reason, it is important to have CO mediators, in order to protect HCPS' right of refusal to treat and ensure that this type of position on the part of HPC has a lesser impact on patients. Moreover, it can also be argued that the refusal to perform certain medical procedures by HCPs can place patients in a situation of unequal access, especially in rural and remote areas, where access to health care is not as in-depth [13].…”
Section: Introductionmentioning
confidence: 99%